Linguistically Modulated Perception and Cognition: The Label-Feedback Hypothesis - Lupyan, Gary (Frontiers in Psychology, 2012)
How does language impact cognition and perception? A growing number of studies show that language, and specifically, the practice of labeling, exerts rapid and pervasive effects on putatively nonverbal processes such as categorization, visual discrimination, and simple detection. Progress on the empirical front, however, has not been accompanied by an increased understanding of the mechanisms by which language affects these processes. Among the puzzles is how the effects of language can be both deep in the sense of affecting even basic visual processes, and yet vulnerable to manipulations such as verbal interference which can sometimes nullify effects of language. In this paper, I review some of the evidence for effects of language on cognition and perception, showing that sensory processes that have been presumed to be language-free are in fact rapidly and pervasively affected by language. I argue that a clearer understanding of the relationship between language and cognition can be achieved by rejecting the distinction between verbal and nonverbal representations and adopting a framework in which language modulates ongoing cognitive and perceptual processing.